PERAN LITERASI, PERILAKU, DAN TEKNOLOGI TERHADAP INKLUSI KEUANGAN YANG DIMEDIASI OLEH MODAL INTELEKTUAL - Dwi Prayoga, Ryan; Padmantyo, Sri (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This study aims to make an important contribution to understanding the dynamics of financial inclusion among university students, particularly in the city of Surakarta. Focusing on the level of financial literacy, financial behavior and financial technology, this study aims to identify the extent to which these factors influence financial inclusion through intellectual capital. This study shows that financial literacy has a positive impact on financial inclusion, suggesting that a good understanding of financial concepts encourages more active participation in financial services. Financial behavior also plays an important role in building financial inclusion. Smart behavior in terms of spending, wealth management and investment decisions can improve students' access to financial services that meet their needs. The importance of financial technology in the context of financial inclusion is also apparent from the results of this study. The use of financial technology provides students with more effective and efficient access to financial services, thus expanding opportunities for financial inclusion in the digital age. The implications of these results can inform educational institutions, governments, and financial service providers to develop better strategies to improve student financial inclusion.